Determinants of Bank Performance in Indonesia - Usman, Bahtiar; Lestari, Henny Setyo (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2019)
This study aims to examine the determinants of commercial banks’ performances in Indonesia in the period 2008-2017 by their return on assets. Capital adequacy, asset quality, management efficiency and liquidity, and gross domestic product functioned as the predictors. The sample of this study was 25 conventional banks meeting the criteria of the purposive sampling method. The panel data with Eviews shows that asset quality has a negative effect and management efficiency has a positive impact on bank performance. Capital adequacy, liquidity, and gross domestic product growth rate do not affect the bank's performance. Managers need to tighten lending, carry out credit restructuring and manage the balance between assets and liabilities and, supervise credit.